The influence of silane surface modification on microcrystalline cellulose characteristics - Neves, Roberta Motta; Ornaghi, Heitor Luiz [UNESP]; Zattera, Ademir José; Amico, Sandro Campos (Elsevier, 2020)
Microcrystalline cellulose (MCC) can be a reinforcement in composites, especially after surface modification. In this paper, MCC was modified using 3-aminopropyltriethoxysilane (APTES) in the following ratios (MCC/APTES): 1:3, 1:4, 1:5, 1:10). The MCC morphologies did not change with the treatment even though the distribution of APTES over the MCC surface varied. FTIR analysis showed MCC and APTES characteristic peaks for all samples. The crystallinity index (CI) decreased with the APTES ratio. The non-isothermal kinetic degradation by thermogravimetric analysis in different heating rates was studiedin order to evaluate the kinetic triplet: activation energy Ea, exponential factor (A), and reaction order (f(α)). The Ea dependence on conversion degree was not affected, but two degradation steps were observed for all samples. Ratios up to 1:4 suggested two consecutive autocatalytic degradation mechanisms. The 1:5 and 1:10 ratios caused a change in the most probable degradation mechanism for nucleation followed by autocatalytic degradation mechanism.
Keywords: Degradation mechanism; Kinetics; Microcrystalline cellulose; Silane; Surface modification